Comparative Analysis of Shakespearean Tragic Hero: Othello vs. Hamlet - Khandelwal, Shilpa; ., Kulbhushan (Journal of Advanced Research in English & Education, 2020)
A tragic hero is usually the central character in any play. Hamlet and Othello are two of Shakespeare’s most popular plays and are similar to each other in some aspects, tragedy being their basic theme. In this paper a Comparative Analysis of Shakespearean Tragic Hero: Othello vs. Hamlet has been carried out. The main characters of these tragedies possess different traits; and all can be described as tragic Shakespearean heroes and basically good and noble men whose tragic flaw leads to their destruction. How to cite this article:  Khandelwal S, Kulbhushan. Comparative Analysis of Shakespearean Tragic Hero: Othello vs. Hamlet. J Adv Res Eng & Edu 2019; 4(4): 1-5. DOI: https://doi.org/10.24321/2456.4370.201907